Navigating the Challenges of Acanthamoeba Keratitis: Current Trends and Future Directions - Lanxing Fu; Joanna Wasielica-Poslednik; Gerd Geerling; Scott Robbie; Fabiana D’Esposito; Mutali Musa; Daniele Tognetto; Rosa Giglio; Caterina Gagliano; Marco Zeppieri (Life, 2025)
Acanthamoeba keratitis (AK) is a vision-threatening eye infection induced by the free-living species of the amoeba genus Acanthamoeba, presenting considerable therapeutic difficulties due to its frequently delayed diagnosis, chronic nature, and resistance to standard treatments. This review examines the changing landscape of AK, emphasizing recent developments in pathogenesis, diagnosis, and treatment. We examine the molecular pathways that enable Acanthamoeba invasion and persistence in the cornea, and how comprehending these processes can inform the creation of more effective treatment therapies. The review emphasizes current advancements in diagnostic methodologies, such as PCR-based tests and in vivo confocal imaging, which have enhanced early detection rates and diagnostic precision. Furthermore, we analyze contemporary treatment modalities, including antimicrobial therapy and surgical procedures, while recognizing the difficulties presented by antimicrobial resistance and the lack of standardized treatment protocols. This review seeks to deliver a thorough examination of AK, presenting insights into cutting-edge treatments and pinpointing essential areas for future research to address the persistent hurdles in controlling this potentially devastating ocular infection.